Speciation Study on O-Phosphorylethanolamine and O-Phosphorylcholine: Acid–Base Behavior and Mg2+ Interaction - Aiello, Donatella; Cordaro, Massimiliano; Napoli, Anna; Foti, Claudia; Giuffrè, Ottavia (Frontiers in Chemistry, 2022)
In the present study the acid-base behavior of compounds constituent the headgroups of biomembranes, O-phosphorylethanolamine (PEA) and O-phosphorylcholine (PPC), was investigated by potentiometric titrations in NaCl aqueous solutions at different temperature (15 ≤ t / °C ≤ 37) and ionic strength (0.15 ≤ I / mol L-1 ≤ 1) values. The complexation properties and the speciation of these ligands with Mg2+ were defined under different temperatures (15 ≤ t / °C ≤ 37) and I = 0.15 mol L-1. The results evidenced the formation of three species for PEA, namely MLH2, MLH and ML and two species for PPC, namely MLH and ML. 1H-NMR titrations were performed on solutions containing ligand and metal-ligand solutions at t = 25°C and I = 0.15 mol L-1. The estimated values of the ligand protonation and complex formation constants and the speciation model are in accordance with the potentiometric data. The enthalpy changes were also determined at t = 25°C and I = 0.15 mol L-1 by the dependence of formation constants on the temperature, confirming the electrostatic nature of the interactions. Matrix assisted laser desorption mass spectrometry (MALDI-MS) was applied for the characterization of Mg2+-L systems (L= PEA or PCC). MS/MS spectra of free ligands and of Mg2+-L species were obtained. The observed fragmentation patterns of both Mg2+-L systems allowed to elucidate the interaction mechanism that occurs via the phosphate group generating a four membered cycle.